2013
DOI: 10.1111/nph.12321
|View full text |Cite
|
Sign up to set email alerts
|

Increased vapor pressure deficit due to higher temperature leads to greater transpiration and faster mortality during drought for tree seedlings common to the forest–grassland ecotone

Abstract: SummaryTree species growing along the forest-grassland ecotone are near the moisture limit of their range. Small increases in temperature can increase vapor pressure deficit (VPD) which may increase tree water use and potentially hasten mortality during severe drought.We tested a 40% increase in VPD due to an increase in growing temperature from 30 to 33°C (constant dewpoint 21°C) on seedlings of 10 tree species common to the forest-grassland ecotone in the southern Great Plains, USA.Measurement at 33 vs 30°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
149
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(155 citation statements)
references
References 33 publications
4
149
0
2
Order By: Relevance
“…There are more trees still alive at higher elevations with concomitant lower temperatures and greater rainfall. It has been demonstrated that a small increase in temperature can increase vapour pressure deficit (VPD) which increases tree water use resulting in an increase in mortality during severe drought due to xylem cavitation [33]. This increased mortality with increased temperature is also demonstrated by our model showing a significant increase in mortality on warmer north facing slopes.…”
Section: Discussionsupporting
confidence: 72%
“…There are more trees still alive at higher elevations with concomitant lower temperatures and greater rainfall. It has been demonstrated that a small increase in temperature can increase vapour pressure deficit (VPD) which increases tree water use resulting in an increase in mortality during severe drought due to xylem cavitation [33]. This increased mortality with increased temperature is also demonstrated by our model showing a significant increase in mortality on warmer north facing slopes.…”
Section: Discussionsupporting
confidence: 72%
“…For anisohydric A. auriculiformis and E. citriodora, their water use strategy was conservative, imparted minimal effects on regional hydrological budget under current meteorological and soil conditions. The temperature or D would inevitably be enhanced under land use and global climate warming scenarios (Kalnay and Cai, 2003;Will et al, 2013), which probably increases the water use of timber trees, but has little effects on water flux of mature trees (Kagawa et al, 2009). In conclusion, the specific tree hydraulic architectures such as the resistance to embolism, the sensitivity to D, and the regulator (wood density in this research) of G sref should be considered when quantifying the influences of land use changes on water flux.…”
Section: Resultsmentioning
confidence: 95%
“…stomatal conductance; g s ). Plants protect themselves from excessive water losses (diffusion out of the leaf) under water-limited environments through a reduction of stomatal conductance, which in turn leads to less carbon uptake (diffusion of CO 2 into the leaf) and possibly subsequent physiological stress (McDowell et al, 2008;Will et al, 2013).…”
Section: Introductionmentioning
confidence: 99%